Efficient Conversion of Lignin to Electricity Using a Novel Direct Biomass Fuel Cell Mediated by Polyoxometalates at Low Temperatures - Zhao, Xuebing; Zhu, J. Y. (ChemSusChem, 2016)
A novel polyoxometalates (POMs) mediated direct biomass fuel cell (DBFC) was used in this study to directly convert lignin to electricity at low temperatures with high power output and Faradaic efficiency. When phosphomolybdic acid H3PMo12O40 (PMo12) was used as the electron and proton carrier in the anode solution with a carbon electrode, and O2 was directly used as the final electron acceptor under the catalysis of Pt, the peak power density reached 0.96 mW cm−2, 560 times higher than that of phenol‐fueled microbial fuel cells (MFCs). When the cathode reaction was catalyzed by PMo12, the power density could be greatly enhanced to 5 mW cm−2. Continuous operation demonstrated that this novel fuel cell was promising as a stable electrochemical power source. Structure analysis of the lignin indicated that the hydroxyl group content was reduced whereas the carbonyl group content increased. Both condensation and depolymerization takes place during the PMo12 oxidation of lignin. POMs full of energy! Polyoxometalates (POMs) mediated direct biomass fuel cells (DBFC) are used to directly convert lignin to electricity at low temperatures with high power output and Faradaic efficiency. Continuous operation demonstrated that the fuel cells are promising as a stable electrochemical power sources. Both condensation and depolymerization took place during the POM oxidation of lignin.